'There are two gaps, so': teaching materials as resources for correction in pre-service teachers' EFL classes. Issue 1 (3rd April 2021) - Tůma, František; Lojdová, Kateřina
ABSTRACT: This study investigates how pre-service teachers of English as a foreign language do correction during their initial teaching practice at lower-secondary schools. The study employs multimodal conversation analysis on a dataset of 16 lessons taught by three pre-service teachers in Czechia. The analysis focuses specifically on how the teachers orient to the task format when doing correction in answer-check sequences. It demonstrates how the teachers employ talk, gesture and gaze to make the task format (such as fill-in-the-blanks, matching) relevant and thereby use the materials as points of reference as well as resources for structuring classroom discourse. This use of materials contributes to the completion of the correction sequences. It is concluded that (over-)reliance on teaching materials and limited flexibility, which can be observed in not accepting alternative answers produced by learners, seem to be manifestations of some of the traits of pre-service teachers' performance.